Large-scale data analysis on endometriosis from the UK Biobank reveals novel genetic loci - Rahmioglu, N; Cook, J; Becker, C; Morris, A; Zondervan, K (SAGE Publications, 2018)
Endometriosis is a common complex condition with an estimated heritability of 50%. The largest meta-analysis of genome-wide association studies (GWAS) for endometriosis to date, including 17K cases, identified 14 genome-wide significant loci (p<5x10-8) together explaining only 5% of the heritability. In ongoing analyses we are substantially increasing sample size by including novel datasets such as the UK Biobank. The UK Biobank involves medical records and self-reported questionnaire data on 500,000 volunteer participants, for which the full genotype data, imputed up to the HRC reference panel, has been recently released.